Optimization of Personnel Management in Banks and Capacity Building Based on Foreign Experience - Abdurahmanov, A. S.; Burxonov, B. S. (Journal of Contemporary Business Law & Technology: Cyber Law, Blockchain, and Legal Innovations, 2024)
This article deals with the management of banks and their capacity building on the basis of foreign experience, further optimization of the industry. Foreign experience in capacity building will also be considered.